Transcriptional analysis of THP-1 cells infected with leishmania infantum indicates no activation of the inflammasome platform - Gatto, Mariana [UNESP] (2020)
Leishmaniasis is caused by intracellular parasites transmitted to vertebrates by sandfly bites. Clinical manifestations include cutaneous, mucosal or visceral involvement depending upon the host immune response and the parasite species. To assure their survival inside macro-phages, these parasites developed a plethora of highly successful strategies to manipulate various immune system pathways. Considering that inflammasome activation is critical for the establishment of a protective immune response in many parasite infections, in this study we determined the transcriptome of THP-1 cells after infection with L. infantum, with a particular focus on the inflammasome components. To this end, the human cell line THP-1, previously differentiated into macrophages by PMA treatment, was infected with L. infantum promasti-gotes. Differentiated THP-1 cells were also stimulated with LPS to be used as a comparative parameter. The gene expression signature was determined 8 hours after by RNA-seq tech-nique. Infected or uninfected THP-1 cells were stimulated with nigericin (NIG) to measure active caspase-1 and TNF-α, IL-6 and IL-1β levels in culture supernatants after 8, 24 and 48 hours. L. infantum triggered a gene expression pattern more similar to non-infected THP-1 cells and very distinct from LPS-stimulated cells. Some of the most up-regulated genes in L. infantum-infected cells were CDC20, CSF1, RPS6KA1, CD36, DUSP2, DUSP5, DUSP7 and TNFAIP3. Some up-regulated GO terms in infected cells included cell coagulation, regulation of MAPK cascade, response to peptide hormone stimulus, negative regulation of transcription from RNA polymerase II promoter and nerve growth factor receptor signaling pathway. Infection was not able to induce the expression of genes associated with the inflammasome signaling pathway. This finding was confirmed by the absence of caspase-1 activation and IL-1β production after 8, 24 and 48 hours of infection. Our results indicate that L. infantum was unable to activate the inflammasomes during the initial interaction with THP-1 cells.